Axonal Injury in the Lateral Geniculate Body: Radiological Diagnosis. (4th July 2017) - Gutiérrez, Laura; Arruga, Jorge; Sánchez, Juan J.; Muñoz, Silvia; Puyalto-de-Pablo, Paloma
ABSTRACT: Damage to the lateral geniculate body by diffuse axonal injury in brain trauma is uncommon. The authors present the clinical case and in vivo fibre tractography using diffusion tensor magnetic resonance imaging of this lesion in a patient presenting with homonymous sectoranopia after a traumatic head injury.